Efficacy in evaluating job performance in a real estate company - López Córdova, Frida Mereyda (2022)
The forms of evaluation of the work performance of the employees for years lacked specific indicators about the attitudes or behaviors of the collaborators and it was carried out every year end; For a better evaluation, the real estate company OPTIMA S.A., proposed an evaluation consisting of a continuous monitoring of performance that would allow timely intervention to regulate processes, train personnel and provide the appropriate stimuli to achieve greater awareness and commitment of the collaborators. To achieve this purpose, a computer module organized based on the ten behaviors of the Behavioral Observation Scale grouped into work, personal and organizational skills was used. The information provided by the team coordinators first showed an efficiency of 96.88% of the collaborators, which was not related to the results of the analysis of the aspects considered in which only 68.7% were competent. 62.6% carried out quality work, perhaps due to teamwork, but it was not carried out by all of them, with the record that 68.8% of them made a partial commitment to the company. It is concluded that the evaluation with the designed module was more effective by providing greater and more precise information on the work, personal and organizational skills that the workers possess, in less time and with less demand for resources.